Identification and characterization of additional flagellin genes from Vibrio anguillarum. - McGee, K (1996)
Previously, the flagellar filament of Vibrio anguillarum was suggested to consist of flagellin A and three additional flagellin proteins, FlaB, -C, and -D. This study identifies the genes encoding FlaB, -C, and -D and a possible fifth flagellin gene that may encode FlaE. The flagellin genes map at two separate DNA loci and are most similar to the four polar flagellin genes of Vibrio parahaemolyticus, also located at two DNA loci. The genetic organization of these two loci is conserved between both organisms. For each gene, in-frame deletions of the entire gene, the 5' end, and the 3' end were made. Mutant analysis showed that each mutation, except those in flaE, caused a loss of flagellin from the filament. However, no obvious structural loss in the filament, as determined by electron microscopy, and only slight decreases in motility were seen. Virulence analysis indicated that all but two of the mutations gave a wild-type phenotype. The 5'-end deletions of flaD and flaE decreased virulence significantly (>10(4)-fold) of infections via both the intraperitoneal and immersion routes. These results indicate that, like FlaA, FlaD and FlaE may also be involved in virulence.